Drug delivery applications of noninvasive imaging : validation from biodistribution to sites of action - Li, Chun, 1963-; Tian, Mei (Physician) (Hoboken, New Jersey: John Wiley & Sons, 2013)
Cost-effective strategies for designing novel drug delivery systems that target a broad range of disease conditions In vivo imaging has become an important tool for the development of new drug delivery systems, shedding new light on the pharmacokinetics, biodistribution, bioavailability, local concentration, and clearance of drug substances for the treatment of human disease, most notably cancer. Written by a team of international experts, this book examines the use of quantitative imaging techniques in designing and evaluating novel drug delivery systems and application.
Introduction to molecular imaging / Vikas Kundra -- PET/SPECT : instrumentation and imaging techniques / Yuan-Chuan Tai -- Photoacoustic tomography and its application in drug delivery and photothermal therapy / Liang Song Lihong Wang -- Raman microspectral imaging for label-free detection of nanoparticle-mediated cellular and sub-cellular drug delivery / Tatyana Chernenko ... [et al.] -- Anatomical and functional MRIi / Edward F. Jackson -- Quantitative imaging in drug delivery / Kooresh Shoghi -- PET imaging of small-molecular-weight drug pharmacokinetics / Stephen M. Moerlein and Zhude Tu -- Imaging peptides, proteins, and antibody delivery / F. L. Giesel and C. Kratochwil -- In vivo imaging and delivery of siRNA / Zdravka Medarova and Anna Moore -- Imaging cell therapy / Yijie Linag and Jeff W.M. Bulte -- Radiolabeled liposomes as drug delivery nano-theranostics / William T. Phillips ... [et al.] -- Polymeric micelles as imaging agents and drug delivery systems / Jun Zhao and Chun Li -- Perfluorocarbon nanoparticles: translating bench opportunities to the clinic / G.M. Lanza ... [et al.] -- Cancer theranostics with hollow gold nanospheres / Wei Lu and Chun Li -- Imaging pulmonary drug delivery / Stephen Newman -- In-vivo imaging for validation of oral dose performance / Fiona McInnes and Howard Stevens -- Role of large animal models in translational studies of imaging and targeted drug delivery / Rajesh K. Uthamanthil and Mei Tian -- Imaging transcatheter delivery to liver tumors / Adil AL-Nahhas, Meeran Naji, Imene Zerizer -- Direct visualization of therapeutic radionuclides distribution using nuclear medicine imaging: i-131 in metastatic thyroid carcinoma / Ho Young Lee ... [et al.] -- Imaging drug delivery to the cns using translational positron emission tomography studies / Chi-Ming Lee, Katarina Varns.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Drug Delivery Systems; Diagnostic Imaging; Radiopharmaceuticals; Diagnostic imaging; Drug delivery systems; MEDICAL -- Pharmacology; Diagnostic imaging; Drug delivery systems; Radiopharmaceuticals; Medicine; Electronic books